Comparison of the prognostic value of immunoinflammation-based biomarkers in patients with gastric cancer - Hirahara, Noriyuki (Oncotarget, 2020)
Background: Systemic immune-inflammation index (SII)—comprising platelet, neutrophil, and lymphocyte count—is an objective and reliable biomarker for predicting the prognosis in cancer patients because it comprehensively reflects the balance between host inflammatory and immune responses. In this study, we clarified the prognostic impact of immunoinflammation-based indices, i. e. SII, neutrophil/lymphocyte ratio (NLR), and platelet/lymphocyte ratio (PLR), in gastric cancer patients. Results: In multivariate analysis, the American Society of Anesthesiologists physical status (ASA-PS) (hazard ratio [HR]: 3.366, p < 0.001), tumor differentiation (HR: 1.705, p = 0.020), pathological Tumor, Node, Metastasis (pTNM) stage (HR: 2.160, p = 0.008), and carcinoembryonic antigen (CEA) (HR: 1.964, p = 0.003) were independent prognostic factors for OS in all patients. Further, multivariate analysis revealed that age (HR: 2.088, p = 0.040), ASA-PS (HR: 2.339, p = 0.043), tumor differentiation (HR: 1.748, p = 0.044), and pTNM stage (HR: 2.114, p = 0.024) were independent prognostic factors for OS among patients without inflammation; SII was not a prognostic factor for OS. Meanwhile, body mass index (HR: 5.055, p = 0.011), ASA-PS (HR: 3.403, p = 0.007), and SII (HR: 4.208, p = 0.026) were independent prognostic factors for OS among patients with inflammation. Materials and Methods: We performed a retrospective review of 412 patients who underwent curative laparoscopic gastrectomy. The prognostic value of SII was compared between a low SII group (SII<661.9) and high SII group (SII≥661.9). We analyzed the predictive ability of immunoinflammation-based indices for overall survival (OS) based on a C-reactive protein (CRP) level of 0.5. Conclusions: Compared to NLR and PLR, SII is the most significant prognostic biomarker for OS, especially in gastric cancer patients with inflammation.